Solvent-free synthesis of Rh/meso-Al2O3 via mechanochemistry for hydrolytic dehydrogenation of ammonia borane. (26th January 2022) - Chen, Junji; Yao, Mengqin; Zou, Qizhuang; Chen, Peng; Liu, Fei; Zhao, Tianxiang
Abstract: An effective strategy synthesis of Rh/meso-Al2 O3 catalysts was demonstrated by mechanochemistry for hydrolytic dehydrogenation of ammonia borane (AB). These catalysts are characterized systematically by N2 adsorption-desorption isotherms, X-ray diffraction (XRD), X-ray photoelectron spectrometry (XPS), scanning electron microscope (SEM), and transmission electron microscope (TEM). The results show that the turnover frequency (TOF) and activation energy ( E a ) are 246.8 molH2 ·molRh −1 ·min −1 and 47.9 kJ mol −1 for hydrolytic dehydrogenation of at 298 K catalyzed by Rh/Al2 O3 -CTAB-400, obviously higher than those previously reported catalysts. Furthermore, catalyst Rh/Al2 O3 -CTAB-400 can be recycled by simple centrifugal separation and the catalytic activity is still well maintained after five cycles. In addition, a plausible mechanism for hydrolytic dehydrogenation of AB has also been proposed. This mechanochemical synthesis method exhibits great application prospects for the preparation of heterogeneous catalysts. Highlights: Solvent-free process produces highly dispersed Rh nanoparticles supported on amorphous mesoporous alumina. Rh/meso-Al2 O3 are synthesized by using a mechanochemical method. Rh/Al2 O3 -CTAB-400 exhibits superior catalytic activity in ammonia borane hydrolysis.